The Influence Of Selling Price And Product Brand On Consumer Purchase Interest (A Case Study at Dapoer Bunda Cenna in Pesawaran) - Charles Wijhaya; Agus Purnomo (Citakonsultindo, 2025)
This study aims to analyze the influence of selling price and product brand on consumer purchase interest in the micro, small, and medium enterprises (MSMEs) Dapoer Bunda Cenna in Pesawaran Regency. Selling price and product brand are considered two main factors that can affect consumers' decisions to purchase a product. This research employs a quantitative method with a survey approach involving 87 respondents who have purchased products from Dapoer Bunda Cenna. Data were collected through questionnaires and analyzed using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, and multiple linear regression to examine the influence of selling price and product brand on consumer purchase interest.The results indicate that the selling price has a positive and significant influence on consumer purchase interest, with a regression coefficient value of 0.241. Similarly, the product brand also has a positive and significant influence, with a regression coefficient value of 0.273. The t-test shows that both independent variables, selling price and product brand, have a significant influence on consumer purchase interest, with a significance value less than 0.05. The ANOVA test also reveals a significant joint effect of selling price and product brand on consumer purchase interest.